Differential effects of Bacillus subtilis– and Bacillus licheniformis–fermented products on growth performance, intestinal morphology, intestinal antioxidant and barrier function gene expression, cecal microbiota community, and microbial carbohydrate-active enzyme composition in broilers - Yu-Wei Chen; Yu-Hsiang Yu (Poultry Science, 2023)
ABSTRACT: This study investigated the differential effects of Bacillus subtilis–fermented products (SFPs) and Bacillus licheniformis–fermented products (LFPs) on the growth performance, intestinal morphology, intestinal gene expression, cecal microbiota community, and microbial carbohydrate-active enzyme composition of broilers. In total, 160 one-day-old unsexed Arbor Acres broiler chicks were randomly allocated to 4 treatment groups (with 8 replicates per group and 5 chicks per replicate): control (CON), enramycin (ENM), SFP, and LFP groups, which were fed a basal diet, basal diet supplemented with 10 mg/kg ENM, basal diet supplemented with 108 colony-forming units (CFU) of B. subtilis spores per gram of feed, and basal diet supplemented with 108 CFU of B. licheniformis spores per gram of feed, respectively. LFP treatment resulted in a higher (P < 0.01) body weight at the age of 35 d and higher average daily gain over 15 to 35 (P < 0.05) and 1 to 35 (P < 0.05) d of age than did the CON and SFP treatments. The average villus heights in the jejunum were longer (P < 0.05) in the LFP group than those in the SFP group. Moreover, the LFP group exhibited a higher jejunal barrier function gene expression (mucin 2, zonula occludens-1, and occludin) and cecal antioxidant gene expression (superoxide dismutase) than did the CON group (P < 0.05). A principal coordinate analysis of cecal microbiota and carbohydrate-active enzyme composition demonstrated distinct clustering among the groups. Lactobacillus crispatus abundance in the cecal digesta was higher (P < 0.01) in the SFP group than in the CON and LFP groups. Finally, microbial glycosyltransferase 2 gene expression in the cecal digesta was higher in the LFP group than in the CON and ENM groups. In conclusion, LFPs can improve the growth performance, increase intestinal barrier function and antioxidant gene expression, and modulate cecal microflora composition and carbohydrate-active enzyme composition of broilers. The overall effect of LFPs on growth promotion in broilers was superior to that of SFPs.